2020
DOI: 10.1177/2058460120962732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reliability of magnetic resonance imaging using cartilage and T1-weighted sequences in the assessment of the closure of the growth plates at the knee

Abstract: Background Growth development is traditionally evaluated with plain radiographs of the hand and wrist to visualize bone structures using ionizing radiation. Meanwhile, MRI visualizes bone and cartilaginous tissue without radiation exposure. Purpose To determine the state of growth plate closure of the knee in healthy adolescents and young adults and compare the reliability of staging using cartilage sequences and T1-weighted (T1W) sequence between pediatric and general radiologists. Material and Methods A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The correlation between the modalities is of interest because previous MRI studies have shown different results in assessing the growth plate, depending on whether the assessment has been performed on a cartilage sequence or T1-weighted sequence. 28 Our study strengthens the hypothesis that the multi-gradient echo 3D sequence accurately reproduces the growth plate on MRI.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The correlation between the modalities is of interest because previous MRI studies have shown different results in assessing the growth plate, depending on whether the assessment has been performed on a cartilage sequence or T1-weighted sequence. 28 Our study strengthens the hypothesis that the multi-gradient echo 3D sequence accurately reproduces the growth plate on MRI.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the high‐resolution histological images showed a small chondrocyte remnant of the growth plate in the rabbits that was completely fused. A growth plate remnant has also been reported in human subjects 28–30 . Our findings indicate a difference between chronological and biological ages.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Images were examined and rated according to a system based on Kellinghaus' modified version of Schmeling's developmental stages 6,7 , and the developmental stages by Dedouit et al 8 with minor alterations. Our scale was introduced in a previous study 21 in which we defined the scale as follows:…”
Section: Image Assessmentmentioning
confidence: 99%
“…Two reviewers independently screened the titles and abstracts identified by the literature search strategy. All studies of potential relevance according to the inclusion criteria Kvist [18] were obtained in full text, and two reviewers independently assessed them for inclusion. In addition, the articles included in the systematic review by Ding et al [25] were screened for relevance.…”
Section: Study Selectionmentioning
confidence: 99%